Prevalence and Predictors of Quality of Ethnic Minority Human Resources in the Central Highlands of Vietnam - Truc, Nguyen Thanh; Vy, Pham Thao; Nga, Huynh Thi; Vuong, Vu Trinh; Hoi, Vo Xuan; Tuan, Tran Anh; Hoa, Ao Xuan (Journal of Ecohumanism, 2024)
This study investigates the prevalence and predictors of ethnic minority human resource (HR) quality in Vietnam’s Central Highlands through a community-based cross-sectional survey across five provinces. The study assessed ten factors: “Overall Quality” (knowledge-KNO, attitude-ATT, skills-SKI, physical strength-PHY) and “Supporting Policies and Conditions” (utilization policy-USA, training and development-TRA, remuneration-REM, standard of living-EAR, working conditions-CON, culture-CUL). Significant relationships were found among the all factors of the group “Supporting Policies and Conditions” (p<0.001 all). Moreover, five factors (USA, TRA, EAR, CON, CUL) with demographic factors such as ethnicity, education, management experience, and years of work showed significant impacts the quality of ethnic minority HR (p<0.05 all). These results highlight the importance of comprehensive policies and targeted training programs to improve the overall quality of ethnic minority human resources, providing valuable insights for policymakers to enhance socio-economic development in Vietnam’s ethnic minority communities.